Characterization of Ti-48Al-2Cr-2Nb built by selective laser melting. (October 2021) - Mizuta, Kazuhiro; Hijikata, Yuta; Fujii, Tatsuya; Gokan, Kazuhiro; Kakehi, Koji
Abstract: Selective laser melting was applied to TiAl4822. Electron beam melting has been a major additive manufacturing process for TiAl4822, but ductility is a technical challenge with EBM. This research investigates the microstructure and the tensile properties of TiAl4822 fabricated by a new SLM machine equipped with a heating unit. The elongation of the SLM specimen was 8.3 times that of the EBM specimen; this was attributable to the γ-phase−based homogeneous fine grains in the SLM. Graphical abstract: Image, graphical abstract